Lipid-Based Nanoformulations for Drug Delivery: An Ongoing Perspective - Mubashar Rehman; Nayab Tahir; Muhammad Farhan Sohail; Muhammad Usman Qadri; Sofia O. D. Duarte; Pedro Brandão; Teresa Esteves; Ibrahim Javed; Pedro Fonte (Pharmaceutics)
Oils and lipids help make water-insoluble drugs soluble by dispersing them in an aqueous medium with the help of a surfactant and enabling their absorption across the gut barrier. The emergence of microemulsions (thermodynamically stable), nanoemulsions (kinetically stable), and self-emulsifying drug delivery systems added unique characteristics that make them suitable for prolonged storage and controlled release. In the 1990s, solid-phase lipids were introduced to reduce drug leakage from nanoparticles and prolong drug release. Manipulating the structure of emulsions and solid lipid nanoparticles has enabled multifunctional nanoparticles and the loading of therapeutic macromolecules such as proteins, nucleic acid, vaccines, etc. Phospholipids and surfactants with a well-defined polar head and carbon chain have been used to prepare bilayer vesicles known as liposomes and niosomes, respectively. The increasing knowledge of targeting ligands and external factors to gain control over pharmacokinetics and the ever-increasing number of synthetic lipids are expected to make lipid nanoparticles and vesicular systems a preferred choice for the encapsulation and targeted delivery of therapeutic agents. This review discusses different lipids and oil-based nanoparticulate systems for the delivery of water-insoluble drugs. The salient features of each system are highlighted, and special emphasis is given to studies that compare them.